The king's procession - McCrea, James; McCrea, Ruth. (New York : Atheneum, 1963)
When Pipin, the stable boy, rode in the King's procession on a skin-and-bones donkey, the villagers laughed and threw sticks at him. When the King found out, he gave him a fine white pony and something else even more important to Pipin.
Keywords: Parades -- Fiction; Parades -- Fiction